The Effect of Return Perception, Motivation, Financial Literacy, and Income on Investment Interest of Students at State University of Jakarta - Melati Widiantika; Umi Mardiyati; Gatot Nazir Ahmad (LPPM Universitas Negeri Jakarta, 2022)
ABSTRACT MELATI WIDIANTIKA, 2021; The Effect of Return Perception, Motivation, Financial Literacy and Income on Investment Interest of Bachelor Degree Students, Class of 2016 and 2017 at State University of Jakarta, 2021. The purpose of this study was to determine the effect of financial literacy, motivation, return perception, and income on investment interest in FE UNJ students, to analyze financial literacy, motivation, perceived return, and income on investment interest in 2016 and 2017 undergraduate students in FE UNJ. The research model used in this study uses descriptive analysis. This research was conducted on 754 students registered as active on bachelor degree students, class of 2016 and 2017 in FE UNJ Study Program, using probability sampling techniques. The data collection technique used a survey method by distributing questionnaires to 261 respondents. The results of SPSS show that there is a significant influence on the perception of return, motivation, financial literacy, and income on investment interest. The results of SPSS showed a significant influence of motivation on investment interest, but on the other hand, the result showing that insignificant between return perception, financial literacy, and income on investment interest. The implications of this research are practical implications and theoretical implications. Practical implications regarding investment interest research are expected to help students, lecturers, faculties, and universities, in providing investment information, providing easy access to information and communication through cooperative relationships between faculty and securities companies, stock exchanges, and interested parties. and similar activities. The theoretical implication of the results of this study is to provide information in the development of knowledge in the fields of financial management, monetary economics, financial literacy, and sharia investment management. Keywords: return perception, motivation, financial literacy, income, investment interest, FE UNJ bachelor degree students.